(3GdJObjb hGdQbGHI GdOGNdjI aj HjFI fXe GdeYdheGJ GdeMGSHjI (B/s - (3GdMSHGf, YWG Gddg GMeO Shjdes ((3YeGf(B: s (3OGQ GdQGjI(B, s, 2009)
(3eJWdHGJ HjFI JcfhdhLjG GdeYdheGJ,fXGe GdQbGHI GdOGNdjI aj Xd HjFI JcfhdhLjG GdeYdheGJ,fXGe GdQbGHI GdOGNdjI aj Xd HjFI JcfhdhLjG GdeYdheGJ,JWhQ OhQ GdJObjb GdOGNdj aj HjFI JcfhdhLjG GdeYdheGJs
(3HHdjhZQGajG(B:(3U U(B.223-231s
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s